Edukasi Tentang Kurang Energi Kronik (KEK) Pada Ibu Hamil Dan Pemberian Isi Piringku Di Dusun 2 Desa Wonokerto Kecamatan Tugumulyo Kabupaten Musi Rawas - Ranti Sartika; Simbolon, Sertyka; Asih , Tri; Yulianti, Syami; Sari, Fikitri Marya (Utami Publisher, 2025)
This study aims to determine the relationship between anemia and the incidence of Chronic Energy Deficiency (CED) in pregnant women in Desa Wonokerto Dusun 2, Kecamatan Tugumulyo, Kabupaten Musi Rawas. Anemia and CED are common health problems in pregnant women that can affect both maternal and fetal health. The research method used is observational with a cross-sectional approach. The sample used in this study consisted of 25 pregnant women from Desa Wonokerto Dusun 2. Data collection was conducted through interviews and nutritional status measurements, including hemoglobin (Hb) tests and upper arm circumference (UAC) measurements to detect CED. Data were analyzed using the Chi-Square test to determine the relationship between anemia and the incidence of CED. The results showed a significant relationship between anemia and the occurrence of CED in pregnant women in Desa Wonokerto (p < 0.05). A decrease in hemoglobin levels in pregnant women increases the risk of developing CED. It is hoped that the findings of this study can serve as a basis to increase attention to maternal health in the area and reduce the prevalence of anemia and CED.